The miracle in the Iron and the Ising model of the Ferromagnet on regular lattice Z^2 - Ganikhodjaev, Nasir (2011)

(untitled)
It is well known that the Qur’an has many miraculous attributes proving that it is revelation from God. In this paper we consider one of them, namely, the miracle in the Iron. One of the main and very useful property of the Iron is to be magnet. In 1925 Ising wrote his doctoral thesis on a model now called the Ising model. He tried to explain, using this model, certain empirically observed facts about ferromagnetic materials. In this paper we present the basic ideas of the Ising model on regular lattice , which has been starting point of the theory of lattice models of Statistical Mechanics, and show the existing of spontaneous magnetization effect.